2020
DOI: 10.1007/s10340-020-01230-w
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopy provides visual evidence and confirms the feasibility of dsRNA delivery to emerald ash borer through plant tissues

Abstract: Double-stranded RNA (dsRNA)-mediated gene silencing, or RNA interference (RNAi), is an emerging biotechnology that has been a breakthrough tool for crop protection. Exogenous dsRNA triggers the RNAi pathway, silences genes, disrupts protein function, and can cause insect mortality. However, effective delivery of the dsRNA is problematic, particularly in systems with long-lived, endophagous insects such as the emerald ash borer (EAB), Agrilus planipennis, a tree-killing nonnative invader that attacks ash, Fraxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Safety protocols dictate that exposures used for toxicity studies with non-target arthropods must exceed the maximum amount of dsRNA expected to be available in the environment (EFSA European Food Safety Authority, 2014). Previous studies demonstrated that adult EAB experiences significant gene silencing and mortality when exposed to ash leaves treated with dsRNA solution at 70 ng/µl (Pampolini et al, 2020). In the present study, our model NTOs were exposed to EAB dsRNAs in diets at concentrations ∼140 times higher than that inducing mortality in EAB delivered topically on plant foliage.…”
Section: Synthesismentioning
confidence: 85%
See 3 more Smart Citations
“…Safety protocols dictate that exposures used for toxicity studies with non-target arthropods must exceed the maximum amount of dsRNA expected to be available in the environment (EFSA European Food Safety Authority, 2014). Previous studies demonstrated that adult EAB experiences significant gene silencing and mortality when exposed to ash leaves treated with dsRNA solution at 70 ng/µl (Pampolini et al, 2020). In the present study, our model NTOs were exposed to EAB dsRNAs in diets at concentrations ∼140 times higher than that inducing mortality in EAB delivered topically on plant foliage.…”
Section: Synthesismentioning
confidence: 85%
“…Implementation of crop protection strategies applying RNAi technology are under development (Poelchau et al, 2016;Vogel et al, 2019). Potential applications of environmental or dietary RNAi for pest control include applications of dsRNA in foliar sprays (San Miguel and Scott, 2016); systemic uptake through plant material (Hunter et al, 2012;Dalakouras et al, 2018;Pampolini et al, 2020), oral administration of dsRNA in baits (Zhou et al, 2008), embedded in nanoparticles (Zhang et al, 2010;Yan et al, 2020), expressed in genetically engineered microorganisms (Zhu et al, 2011;Joga et al, 2016), or expressed in transgenic plants (Baum et al, 2007;Mao et al, 2007;Ghag, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant bacteria with EAB-specific dsRNA could be sprayed on foliage to be ingested by feeding beetles or on ash stems to be ingested by newly hatched neonates. Naked dsRNAs applied topically or through root drenching can be assimilated into and moved through ash plant tissues [ 27 ], suggesting crude extract of bacterially-expressed dsRNA may also be able to be translocated through the plant via soil drench, trunk sprays or injection [ 28 ]. Recombinant bacteria producing EAB-specific dsRNAs also make the genetic transformation of ash trees with dsRNA-expressing constructs a more plausible goal [ 29 ].…”
Section: Discussionmentioning
confidence: 99%